CONDITIONS DO AND BOD5 IN REARING TANKS OF (Pangasianodon hypopthalmus) TREATED WITH PHOTOPERIOD MANIPULATION AND BIOFLOC SYSTEM - Melisa Berliana; Budijono Budijono; Windarti Windarti (Berkala Perikanan Terubuk, 2021)
Rearing Pangasius hypopthalmus under short manipulated photoperiod is able to improvethe growth of that fish, but the water quality of those rearing tanks were poor as there wasno phytoplankton to reduce the organic materials. By using the biofloc system, the organicmaterials might be processed and the water quality might be maintained. To understand thewater quality of P. hypopthalmus reared in the tanks with manipulated photoperiod andbiofloc system has been conducted in June to august 2020. Sampling DO and BOD5 wascarried out 4. Results shown that the DO of tanks with biofloc system was higher (11.814.49mg/L)thanthatofthetankswithoutbioflocsystem(11.81-7.68mg/L).ThewaterinthetankswithbioflocsystemalsoshownbetterresultsonBOD5(4.28-7.68mg/L).Inthetankswithout the biofloc system, the water quality parameters were as follows BOD5(4.28-35.22 mg/L). Based on data obtained, it can be concluded that the application ofbiofloc system is effective to maintain the water quality in the rearing tank of P.hypopthalmus treated with short photoperiod.